1984
DOI: 10.2337/diacare.7.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Vascular Reactivity to Ischemia in Diabetic Microangiopathy

Abstract: To investigate vascular responses in insulin-dependent diabetic patients both with and without retinopathy, we have assessed vasodilation by forearm transcutaneous pO2 measurement after 10 min of ischemia produced by a sphygmomanometer cuff. Diabetic patients with proliferative retinopathy had a delayed vasodilatory response at 60 s (mean +/- SD pO2 = 9 +/- 3 mm Hg) compared with those having diabetes without retinopathy (15 +/- 4 mm Hg, P less than 0.01) and matched normal subjects (14 +/- 4 mm Hg, P less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Most [23,24], but not all [25,26] studies have found endothelial function to be more markedly impaired in subjects with microalbuminuria or established nephropathy, but, to our knowledge, the current study is the first to report impaired endothelial function in normoalbuminuric subjects with retinopathy compared with those with no retinopathy. The findings are in agreement, however, with one previous study in Type 1 diabetic patients, which did not exclude subjects with microalbuminuria, and found that vasodilation (assessed by forearm transcutaneous pO 2 measurement) in response to ischaemia was reduced in patients with proliferative retinopathy, compared with those with no retinopathy [27]. These observations are relevant because, firstly, they highlight the relationship between endothelial dysfunction and microvascular disease, and secondly, they suggest that the presence of retinopathy may represent a generalized process of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Most [23,24], but not all [25,26] studies have found endothelial function to be more markedly impaired in subjects with microalbuminuria or established nephropathy, but, to our knowledge, the current study is the first to report impaired endothelial function in normoalbuminuric subjects with retinopathy compared with those with no retinopathy. The findings are in agreement, however, with one previous study in Type 1 diabetic patients, which did not exclude subjects with microalbuminuria, and found that vasodilation (assessed by forearm transcutaneous pO 2 measurement) in response to ischaemia was reduced in patients with proliferative retinopathy, compared with those with no retinopathy [27]. These observations are relevant because, firstly, they highlight the relationship between endothelial dysfunction and microvascular disease, and secondly, they suggest that the presence of retinopathy may represent a generalized process of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Although a clear extension of the animal results to human patients may not be possible, it does appear that some correlation may be present. Several studies of the effects of diabetes on vascular reactivity to various stimuli have been published (16,17,(25)(26)(27). In all of these studies, indirect noninvasive assessments of microvascular function appeared to reveal functionally significant changes in vascular reactivity associated with the development of diabetes in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ewald et al [29] showed delayed postischemic hyperemia as monitored by transcutaneous measurement of PO 2 (tcPO 2 ) in children with T1D without signs of vascular disease. In contrast, Haitas et al found lower tcPO 2 in diabetic patients with proliferative retinopathy [30], though tcPO 2 was normal in newly diagnosed T1D with absence of retinopathy.…”
Section: Discussionmentioning
confidence: 86%